Materials on the colour pattern variability of Mesobuthus eupeus (C.L. Koch, 1839) (Arachnida: Scorpiones) in southeastern Shirvan and Gobustan (Eastern Azerbaijan) - N.E. Novruzov (Кавказский энтомологический бюллетень, 2022)
The article presents preliminary results of study of the colour pattern variability of mottled scorpion Mesobuthus eupeus (C.L. Koch, 1839) in habitats of the eastern part of Azerbaijan. The studies were carried out on the basis of material from five samples taken in the southeastern part of the Shirvan Plain, northwestern, northeastern, central and southeastern Gobustan. The colouration of the mottled scorpion is a complex of multi-element characters, which includes the colour and pattern of the dorsal and ventral surfaces of the body. When studying the material, the general colour of background of the body and individual elements of the pattern of the dorsal surface of the mesosome, medial, paramedial and marginal longitudinal stripes, transverse stripes and pigmented areas (spots), were mainly taken into account. Most specimens in samples had all or only part of the pattern elements, the variability of a combination of which led to the formation of a wide variety of colour options. In about 1.2% of specimens, the absence of pattern elements was noted. According to the totality of features (pattern elements) of the dorsal surface of the mesosome, all variable specimens of M. eupeus in the studied material were grouped into 11 morphs, each of which had from 2 to 8 (54 in total) colour aberrations. The frequencies of the variability of the main elements of the pattern were in the range of 0.33–0.84. The relative pigmentation index used to quantify the level of pigment on the mesosomal segments also varied widely (0–0.89; M = 0.36). The polymorphism of colouration and colour pattern of the mottled scorpion, presumably, is the result of adaptation of the species to microbiotopic conditions in habitats in each conglomeration by changing the ratio between the phenotypes presented in them. The manifestation of polymorphism in the colour pattern of the mottled scorpion in a relatively small area can be explained by the spatial differentiation of different types of habitats due to the heterogeneity of a landscape.